Higher education accountability - Kelchen, Robert (Baltimore Johns Hopkins University Press, 2018)
As the price tag of higher education continues to rise, colleges and universities across the country are under increasing pressure to demonstrate their value. State and federal governments demand greater accountability. Foundations and private donors, as well as today's parents and students, approach education with a consumer sensibility. ...Robert Kelchen delivers [a]... comprehensive overview of how college sin the United States came to face such overwhelming scrutiny. Beginning with the earliest efforts to regulate schools, Kelchen reveals the rationale behind accountability and outlines the historical development of how federal and state policies, accreditation practices, private-sector interests, and internal requirements have become so important to institutional success and survival. -- back cover.
Introduction: the retionale for accoutability in higher education -- The theoretical underpinnings of accountability -- The historical development of higher education accountability -- Federal accountability policies -- State accountability policies -- Accreditation and accountability -- Private-sector accountability -- Institutional accountability policies and practices -- Ten lessons learned from accountability policies -- The future of higher education accountability.
Includes bibliographical references and index.
Keywords: Educational accountability; Education, Higher -- Standards; Education, Higher -- Finance